A SEMIOTIC ANALYSIS ON GREENFIELDS FARMING PHILOSOPHY - I Gusti Ayu Agung Arie Puspita Dewi; Ida Ayu Mela Tustiawati (Jurnal Scientia, 2023)
Communication is a common form of human interaction that occurs on a daily basis. Communication has meaning in the science of signs as well. Advertising is an example of a sign. Greenfield’s Farming Philosophy is an audiovisual advertisement that extends for four minutes and fifty-five seconds. This research utilizes a qualitative approach based on Saussure's semiotics theory, as cited by Chandler [1], to examine the meanings of signs in advertisements using Barthes' [2] theory of meaning and Wierzbicka's (1996) theory of color. This research revealed three verbal signs and three visual signs. Each sign has a denotative and connotative meaning.